BENTUK PENYAJIAN TARI BAKONCONG PADA RITUAL PERKAWINAN SUKU DAYAK BADAMEA DESA SANATAB KEBUPATEN SAMBAS - Yusika Linda; Winda Istiandini; Ismunandar Ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe background of this research was Forms of Bakoncong Dance Presentation on Traditional Marriage Rituals in Dayak Badamea Tribe, Sanatab Village, Sajingan Besar District, Sambas Regency. This research used descriptive method with qualitative research as research design and used a choreographic approach because the choreographic approach could relate the researchers' discussion to research problems that lead to the arrangement of dance, and became a form of dance presentation.. Data collecting techniques used observation, interview, and documentation. The technique examined the validity of the data using extended observations and triangulation of sources. Data analysis techniques in the form of analysis during data collection and analysis after data collection. Based on the data analysis, concluded that Bakoncong Dance had elements found in other forms of presentation were, Circular floor design, Group composition using unison design, Bakoncong dance theme was about marriage rituals, Outdoor performances, Governance natural makeup, Women's clothing that was used the Kebaya clothes, Batik-patterned skirts, and small handkerchiefs, Musical accompaniment was used Gong, Tambourine, and Violin and chanting lyrics. The results of this research were expected to be contributed as instructional media material in the form of video performances in learning Art and Culture at VIII SMP. Keywords: Bakoncong,  Form of Presentation,  Kecamatan Sajingan Besar,                    Sanatab